India at the Crossroads : Sustaining Growth and Reducing Poverty - Reynolds, Patricia.; Towe, Christopher (International Monetary Fund, 2001)
The authors examine the numerous structural and policy changes Indian authorities have adopted since the 1991 balance of payments crisis; how these changes helped India weather the Asian financial crisis of 1997-98; the risks to fiscal sustainability and their implications for growth; the challenges facing monetary policy in the face of financial market liberalization; and the benefits of structural reform and fiscal policy for growth, poverty, and the reduction of regional disparities.